How do social and personal identity, sense of place, connectedness to nature and environmental understanding influence the implementation of collective, large-scale biodiversity stewardship initiatives in South Africa? - Potts, Tracey Ann (Rhodes University, Faculty of Science, Department of Environmental Science, 2016)
Biodiversity stewardship is a mechanism that is used to conserve high value biodiversity assets. Biodiversity stewardship programmes focus on areas that are under immediate threat from development or under medium to long term threat from degradation or transformation that will result in habitat loss. Biodiversity stewardship provides a solution to the resource crisis being faced by many state and provincial conservation agencies, NGO's (Non-Governmental Organisations) and PBO's (Public Benefit Organisations) in that it facilitates the declaration, and the subsequent improved conservation management, of private or communally owned land whilst still retaining the existing tenure. The rate of habitat loss can often be slowed, or even reversed, by proactively securing these areas and facilitating management decision-making with a focus on biodiversity outcomes without the capital investment required by the State to purchase the land. In return for conservation management actions, certain land-use restrictions and the associated opportunity costs, the State offers a suite of incentives and benefits that are, where possible, tailored to meet the needs of the landowner. Particular regions of South Africa lend themselves well to the development of biodiversity stewardship initiatives which are designed to secure ecological processes and ecosystems across a landscape or an ecological feature at scales of tens of thousands of hectares. When developing landscape level biodiversity stewardship initiatives, negotiations tend to be focussed on groups of landowners. This requires collaboration and the collective alignment of natural resource management decision-making and conservation actions amongst neighbours. Gaining a better understanding of how the social constructs of ecological understanding, place attachment, connectedness to nature, occupational identity and social and personal identity influence decision-making, behaviour and group structure is a critically important factor when developing a tool to predict the likelihood of landowners to collectively commit to long-term, legally binding biodiversity stewardship programmes. The overarching hypothesis was that the social constructs listed above influence group dynamics within the context of collective pro-conservation behaviour. Social dynamics associated with large-scale biodiversity stewardship initiatives become complex when multiple landowners are involved. Could social cohesion and group culture be influenced by aspects of identity and do these in turn develop into barriers or motivators to coordinated and sustained conservation efforts? Further influences on the successful implementation of landscape scale biodiversity stewardship initiatives could include ecological understanding, connectedness to nature and place attachment. Structured interviews were held with the landowners engaged in two separate large-scale biodiversity stewardship sites, the Compassberg Protected Environment and the Baviaanskloof Hartland, in the Eastern Cape Province of South Africa. The interviews were followed up with surveys containing psychometric scales related to the influence of ecological understanding, place attachment, connectedness to nature and aspects of identity on commitment to collective long-term, large-scale biodiversity stewardship initiatives. The results from a set of non-parametric (exact) Wilcoxon rank-sum tests showed that scores on the new ecological paradigm scale and the place attachment scale latent variables were significantly different at the two study sites, at the 10% level of significance. Demographic differences between the two study sites influenced group dynamics, collective decision-making and commitment. The relationship between the latent variables (the five psychometric scales measured) and the ancillary variables (the demographic data describing the respondents) cannot be considered conclusive; however they do provide relatively useful insights into the development of a scale or tool to measure conservation opportunity. The thesis concludes with a proposed conservation opportunity assessment tool that can be utilised alongside the existing, well refined, conservation priority assessment tools to assist in decision-making when planning large, landscape scale biodiversity stewardship initiatives in South Africa.
Keywords: Uncatalogued